Composite powder for thermal barrier coating, thermal barrier coating and preparation method

By using a spherical composite powder with hollow structure and a composite tantalate with the chemical formula (Hfx, Zr1-x)6Ta2O17, a thermal barrier coating was prepared, which solved the problems of high thermal conductivity and insufficient high-temperature phase structure stability of the existing thermal barrier coating materials, and achieved the effect of significantly reducing thermal conductivity and improving high-temperature stability.

CN119683998AActive Publication Date: 2025-03-25BGRIMM ADVANCED MATERIALS SCI & TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510200206.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-03-25
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

The existing thermal barrier coating materials have high thermal conductivity, which is difficult to meet the thermal insulation requirements, and the high-temperature phase structure is limited, resulting in the coating being prone to failure.

Method used

A spherical composite powder with a hollow structure and a composite tantalate with the chemical formula (Hfx, Zr1-x)6Ta2O17, wherein x is 0.2~0.8. The coating is formed by plasma spheroidization preparation method, which significantly reduces thermal conductivity and improves the stability of the high-temperature phase structure.

Benefits of technology

It significantly reduces the thermal conductivity of the thermal barrier coating and significantly improves the stability of the high-temperature phase structure, extends the life of the coating, and can withstand high-temperature and harsh service environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683998A_ABST
    Figure CN119683998A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of thermal barrier coatings, and particularly relates to composite powder for a thermal barrier coating, the thermal barrier coating and a preparation method. The composite powder is spherical-like powder with a hollow structure, the composite powder comprises composite tantalate with the chemical formula of (Hfx, Zr1-x) 6Ta2O17, and x ranges from 0.2 to 0.8. The thermal barrier coating formed by spraying the composite powder has the advantages that the thermal conductivity is obviously reduced, the high-temperature phase structure stability is obviously improved, and the service life of the thermal barrier coating can be obviously prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermal barrier coatings, in particular to composite powder for thermal barrier coatings, thermal barrier coatings and a preparation method thereof. Background Art

[0002] The development level of aircraft engines is a concentrated reflection of a country's industrial foundation, scientific and technological level, and comprehensive national strength. At present, the turbine inlet temperature of advanced aircraft engines is close to 2000℃, and the temperature reaching the surface of the turbine blades is 1400℃. With the continuous development of engine technology and the continuous improvement of thrust-to-weight ratio, the service temperature will be further increased. The high-temperature resistant thermal barrier coating on the surface of turbine blades has become a bottleneck for improving the performance of aircraft engines.

[0003] At present, the main thermal barrier coating material in service is yttria partially stabilized zirconia (YSZ), but YSZ has a high thermal conductivity and is difficult to meet the thermal insulation requirements of thermal barrier coatings. It is also prone to phase change and sintering when the operating temperature exceeds 1200°C, resulting in coating failure.

[0004] It should be noted that this part of the present invention only provides background technology related to the present invention and does not necessarily constitute prior art or known technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of existing thermal barrier coating materials, such as high thermal conductivity, difficulty in meeting thermal insulation requirements, limited high-temperature phase structure stability, and easy coating failure, and to provide a composite powder for thermal barrier coating, a thermal barrier coating and a preparation method. The thermal barrier coating formed by spraying the composite powder has significantly reduced thermal conductivity and significantly improved high-temperature phase structure stability, and can significantly extend the life of the thermal barrier coating.

[0006] In order to achieve the above-mentioned object, in a first aspect, the present invention provides a composite powder for thermal barrier coating, wherein the composite powder is a spherical powder having a hollow structure, and the composite powder comprises a chemical formula of (Hf x ,Zr 1-x )6Ta2O 17 A composite tantalate, wherein x is 0.2~0.8.

[0007] In some preferred embodiments, the ratio of the inner diameter to the outer diameter of the composite powder is 0.25-0.7.

[0008] Preferably, the ratio of the inner diameter to the outer diameter of the composite powder is 0.4-0.6.

[0009] In a second aspect, the present invention provides a method for preparing the composite powder for thermal barrier coating according to the first aspect, comprising: preparing a Zr 4+ , Hf 4+ 、5+ A composite salt solution, adding a precipitant to the composite salt solution to obtain a suspension, and plasma spheroidizing the suspension to obtain the composite powder for the thermal barrier coating; The composite salt solution contains Zr 4+ , Hf 4+ and Ta 5+ The molar ratio of is 20-40:20-75:15-40, and the solid dispersed phase in the suspension includes a chemical formula of (Hf x ,Zr 1-x )6Ta2O 17 The composite tantalate, x is 0.2-0.8, and the conditions of the plasma spheroidization include: the flame power is 40kW-50kW, and the liquid feeding rate is 5mL / min-15mL / min.

[0010] In some preferred embodiments, the flame power is 42-48 kW, and the liquid inlet rate is 5 mL / min-10 mL / min.

[0011] Preferably, the conditions for plasma spheroidization also include: the gas temperature of the quenching gas for rapid cooling is -15°C to 0°C, and the gas flow rate is 20slpm to 30slpm.

[0012] In some preferred embodiments, a mixture including ZrOCl2·8H2O, HfOCl2·8H2O and TaO(NO3)3 is dissolved in water to prepare the composite salt solution; and the precipitant is ammonia water.

[0013] In a third aspect, the present invention provides a method for preparing a thermal barrier coating, wherein the composite powder for thermal barrier coating described in the first aspect and / or the composite powder for thermal barrier coating prepared by the preparation method described in the second aspect is subjected to atmospheric plasma spraying to obtain a thermal barrier coating.

[0014] In some preferred embodiments, the conditions of the atmospheric plasma spraying include: a spraying distance of 90 mm to 120 mm, a spraying power of 43 kW to 47 kW, a carrier gas flow rate of 2 slpm to 5 slpm, and a powder feeding rate of 10 g / min to 20 g / min; and / or, Before atmospheric plasma spraying using the composite powder for thermal barrier coating described in the first aspect and / or the composite powder for thermal barrier coating prepared by the preparation method described in the second aspect, an MCrAlY coating and a YSZ coating are sprayed in sequence.

[0015] In a fourth aspect, the present invention provides a thermal barrier coating, which is prepared by the preparation method described in the third aspect.

[0016] The composite powder of the present invention comprises a chemical formula of (Hfx ,Zr 1-x )6Ta2O 17 The composite tantalate, in which x is 0.2~0.8, is doped with Hf and Zr in the lattice of Ta2O5, which causes lattice distortion of the original Ta2O5, resulting in long-range disorder and short-range order in the lattice structure within the powder, which reduces the free path of phonons and significantly reduces the thermal conductivity of the coating formed by powder spraying.

[0017] The composite powder of the present invention comprises a chemical formula of (Hf x ,Zr 1-x )6Ta2O 17 The composite tantalate, wherein x is 0.2-0.8, on the one hand, since the main body of the composite powder is tantalum, tantalum has a relatively high melting point, on the other hand, Zr and Hf are doped in the tantalum system, and through the mismatch between the ionic radius and atomic weight of Hf and Zr and tantalum, Hf and Zr atoms are scattered and distributed in the tantalate system, which causes the original lattice to undergo lattice distortion, and the formed phase structure is relatively stable and it is difficult to undergo phase change under high temperature conditions, which can significantly improve the high-temperature phase structure stability of the coating formed by powder spraying and prevent the coating from failing at high temperature. In the present invention, if ZrO2 and / or HfO2 are physically mixed with Ta2O5, since ZrO2 and / or HfO2 are prone to high-temperature phase change at 1100°C-1200°C, from cubic phase to monoclinic phase, volume expansion is caused, and the thermal barrier coating is likely to fail. In the present invention, if only Zr is doped into the lattice of Ta2O5, the stability of the phase structure cannot be effectively improved, the thermal conductivity of the coating cannot be reduced, the fracture toughness of the coating is poor, the brittleness of the coating is large, and the service life of the coating is short. If only Hf is doped into the lattice of Ta2O5, the thermal conductivity of the coating is high, the thermal insulation performance is poor, and the stability of the phase structure cannot be effectively improved. When x is less than 0.2, Zr is dominant, the coating cannot form a ferroelastic domain toughening structure, and thus the fracture toughness of the coating cannot be effectively improved. The phase structure stability formed by the lattice distortion is limited and the thermal conductivity of the coating cannot be effectively reduced. When x is greater than 0.8, Hf is dominant, the coating cannot form a large amount of lattice distortion, the phonons cannot be effectively diffused, the thermal conductivity cannot be effectively reduced and the thermal insulation performance cannot be improved, and the phase structure stability is limited. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0019] Figure 1This is a scanning electron microscope photograph of the composite powder for thermal barrier coating of Example 1 of the present invention.

[0020] Figure 2 This is a scanning electron microscope photograph of the cross section of the composite powder for thermal barrier coating of Example 1 of the present invention.

[0021] Figure 3 This is a scanning electron microscope photograph of the thermal barrier coating of Example 1 of the present invention.

[0022] Figure 4 This is the phase structure diagram of the thermal barrier coating of Example 1.

[0023] Figure 5 This is a phase structure diagram of the thermal barrier coating of Example 1 after high-temperature phase structure stability testing. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] The inventors of the present application have found through research that existing thermal barrier coating materials have high thermal conductivity, are difficult to meet thermal insulation requirements, have limited high-temperature phase structural stability, and are prone to coating failure.

[0026] In this regard, in a first aspect, the present invention provides a composite powder for thermal barrier coating, wherein the composite powder is a spherical powder having a hollow structure, and the composite powder comprises a chemical formula of (Hf x ,Zr 1-x )6Ta2O 17 A composite tantalate, wherein x is 0.2~0.8.

[0027] The inventors found that thermal conductivity decreases with the increase of composition and lattice complexity. The oxide thermal barrier coating conducts heat through lattice vibration (phonon). The thermal conductivity is mainly determined by the free path of phonons. The free path of phonons can be reduced by doping with foreign ions. The average free path of phonons is inversely proportional to the mass difference between the replacing atom and the replaced atom and the square of the ionic radius difference. By introducing anion and cation vacancies and the mismatch between ionic radius and atomic weight through substitution, the introduction of such point defects and the manipulation of atomic arrangement can reduce thermal conductivity. The composite powder of the present invention includes a chemical formula of (Hf x ,Zr 1-x )6Ta2O 17The composite tantalate, in which x is 0.2~0.8, is doped with Hf and Zr in the lattice of Ta2O5, which causes lattice distortion of the original Ta2O5 lattice, resulting in long-range disorder and short-range order in the lattice structure within the powder, which reduces the free path of phonons and can significantly reduce the thermal conductivity of the coating formed by powder spraying.

[0028] The composite powder of the present invention comprises a chemical formula of (Hf x ,Zr 1-x )6Ta2O 17 The composite tantalate, wherein x is 0.2-0.8, on the one hand, since the main body of the composite powder is tantalum, tantalum has a relatively high melting point, on the other hand, Zr and Hf are doped in the tantalum system, and through the mismatch between the ionic radius and atomic weight of Hf and Zr and tantalum, Hf and Zr atoms are scattered in the tantalate system, which causes the original lattice to undergo lattice distortion, and the formed phase structure is relatively stable and it is difficult to undergo phase change under high temperature conditions. Through the interaction of the above two aspects, the high-temperature phase structure stability of the coating formed by powder spraying can be significantly improved, and the high-temperature failure of the coating can be prevented. In the present invention, if ZrO2 and / or HfO2 are physically mixed with Ta2O5, since ZrO2 and / or HfO2 are prone to high-temperature phase change at 1100°C-1200°C, from cubic phase to monoclinic phase, volume expansion is caused, and the thermal barrier coating is likely to fail. In the present invention, if only Zr is doped into the lattice of Ta2O5, the stability of the phase structure cannot be effectively improved, the thermal conductivity of the coating cannot be reduced, the fracture toughness of the coating is poor, the brittleness of the coating is large, and the service life of the coating is short. If only Hf is doped into the lattice of Ta2O5, the thermal conductivity of the coating is high, the thermal insulation performance is poor, and the stability of the phase structure cannot be effectively improved. When x is less than 0.2, Zr is dominant, the coating cannot form a ferroelastic domain toughening structure, and thus the fracture toughness of the coating cannot be effectively improved. The phase structure stability formed by the lattice distortion is limited and the thermal conductivity of the coating cannot be effectively reduced. When x is greater than 0.8, Hf is dominant, the coating cannot form a large amount of lattice distortion, the phonons cannot be effectively diffused, the thermal conductivity cannot be effectively reduced and the thermal insulation performance cannot be improved, and the phase structure stability is limited.

[0029] The composite powder of the present invention is a spherical powder with a hollow structure. The hollow structure can promote the melting of the powder during spraying, reduce the defects of unmelted powder inside the coating, inhibit the stacking of powder that is not fully melted, and improve the bonding strength of the coating (the bonding between the incompletely melted powder and the matrix or other molten powder is mainly mechanical bonding rather than solid solution bonding or chemical bonding); the hollow structure can also be achieved through the powder inheritance mechanism, that is, the internal organizational structure of the powder is retained in the internal organizational structure of the coating. Specifically, after the powder is melted, there is still gas inside the melted powder. After the melted powder is stacked in the coating, it is difficult for the gas to escape, so that pores are dispersed in the coating. The air inside the pores can be regarded as an insulator compared to the coating. The coating has many and diffuse pores, which can further reduce the thermal conductivity of the coating and improve the thermal insulation performance of the coating.

[0030] The composite powder of the present invention has a strength of 50MPa-150MPa, a fluidity of 20s-45s / 50g, and a bulk density of 3.10g / cm 3 ~3.30g / cm 3 .

[0031] In some preferred embodiments, the ratio of the inner diameter to the outer diameter of the composite powder is 0.25 to 0.7. The ratio of the inner diameter to the outer diameter of the composite powder is not less than 0.25, which is more conducive to promoting the melting of the powder during the spraying process, reducing the unmelted particle defects inside the coating, improving the bonding strength of the coating, dispersing pores in the coating, and reducing the thermal conductivity of the coating. The ratio of the inner diameter to the outer diameter of the composite powder is not greater than 0.7, which is more conducive to inhibiting the gasification during the powder spraying process and affecting the coating preparation. The ratio of the inner diameter to the outer diameter of the composite powder refers to the average ratio.

[0032] Preferably, the ratio of the inner diameter to the outer diameter of the composite powder is 0.4 to 0.6. The ratio of the inner diameter to the outer diameter of the composite powder is not less than 0.4, which is more conducive to promoting the melting of the powder during the spraying process, reducing the unmelted particle defects inside the coating, improving the bonding strength of the coating, dispersing pores in the coating, and reducing the thermal conductivity of the coating. The ratio of the inner diameter to the outer diameter of the composite powder is not greater than 0.6, which is more conducive to inhibiting the gasification of the powder during the spraying process and affecting the coating preparation.

[0033] In a second aspect, the present invention provides a method for preparing the composite powder for thermal barrier coating according to the first aspect, comprising: preparing a Zr 4+ , Hf 4+ 、 5+ A composite salt solution, adding a precipitant to the composite salt solution to obtain a suspension, and plasma spheroidizing the suspension to obtain the composite powder for the thermal barrier coating; The composite salt solution contains Zr 4+ , Hf 4+ and Ta 5+The molar ratio of is 20-40:20-75:15-40, and the solid dispersed phase in the suspension includes a chemical formula of (Hf x ,Zr 1-x )6Ta2O 17 The composite tantalate, x is 0.2-0.8, and the conditions of the plasma spheroidization include: the flame power is 40kW-50kW, and the liquid feeding rate is 5mL / min-15mL / min.

[0034] The composite salt solution of the present invention contains Zr 4+ , Hf 4+ and Ta 5+ , Zr 4+ , Hf 4+ and Ta 5+ The molar ratio of is 20~40:20~75:15~40, and a compound salt solution is added which can ionize OH in the solution. - The precipitant is capable of forming a solid dispersed phase comprising a chemical formula (Hf x ,Zr 1-x )6Ta2O 17 The suspension of composite tantalate, x is 0.2~0.8, during the plasma spheroidization process, under the conditions of flame power of 40kW~50kW and liquid feed rate of 5mL / min~15mL / min, the carrier gas feeds the suspension as the feed liquid into the high-temperature plasma, the dispersant (solvent) evaporates rapidly, the solid dispersed phase absorbs heat rapidly, the heat is conducted from the outer surface to the inner surface of the solid dispersed phase, the solid dispersed phase melts from the outer surface to the inner surface, there are a large number of tiny pores inside the solid dispersed phase, the internal gas is difficult to escape, and is enclosed in the internal space, under the action of surface tension, the molten solid dispersed phase particles are condensed into (Hf x ,Zr 1-x )6Ta2O 17 The spherical droplets of composite tantalate; then the spherical droplets containing pores inside enter the cooling chamber for quenching, and the spherical droplet shell is cooled to form a spherical droplet having a chemical formula of (Hf x ,Zr 1-x )6Ta2O 17 The composite tantalate is a spherical powder with a hollow structure.

[0035] The present invention does not limit the carrier gas for plasma spheroidization, such as argon, nitrogen and hydrogen, etc. The quenching of the plasma spheroidization of the present invention preferably uses a quenching gas for rapid cooling, which is more conducive to forming a spherical composite powder with a hollow structure.

[0036] In some preferred embodiments, the flame power is 42-48 kW, and the liquid inlet rate is 5 mL / min-10 mL / min. The degree of melting of the solid dispersed phase in the high-temperature flame is progressive from the surface to the inside. The higher the flame power and the lower the liquid inlet rate, the higher the melting degree of the solid dispersed phase, and the greater the ratio of the inner diameter to the outer diameter of the composite powder. The lower the flame power and the greater the liquid inlet rate, the lower the melting degree of the solid dispersed phase, and the smaller the ratio of the inner diameter to the outer diameter of the composite powder. Under this preferred embodiment, the flame power is 42-48 kW, the liquid inlet rate is 5 mL / min-10 mL / min, and the total amount of heat absorbed by the solid dispersed phase in the high-temperature plasma is controlled, and the degree of melting of the solid dispersed phase is controlled, so that the ratio of the inner diameter to the outer diameter of the composite powder can be 0.25-0.7.

[0037] Preferably, the conditions for plasma spheroidization also include: the gas temperature of the quenching gas is -15°C to 0°C, and the gas flow rate is 20slpm to 30slpm. Under the premise of the flame power of 42 to 48kW and the liquid inlet rate of 5mL / min to 10mL / min, the gas temperature of the quenching gas is -15°C to 0°C, and the gas flow rate is 20slpm to 30slpm, which can make the ratio of the inner diameter to the outer diameter of the composite powder 0.4 to 0.6.

[0038] In some preferred embodiments, a mixture including ZrOCl2·8H2O, HfOCl2·8H2O and TaO(NO3)3 is dissolved in water to prepare the composite salt solution; the precipitant is ammonia water. Under this preferred embodiment, an excess of precipitant is added to the solution, and ammonia water can be decomposed into ammonia gas without impurities at high temperature. Chloride ions and nitrate ions can be combined with ammonium ions and can be thermally decomposed to form gas at a higher temperature, which will not be retained on the powder formed after plasma spheroidization, thereby avoiding the introduction of other impurities and being more conducive to the purification of the powder. In a third aspect, the present invention provides a method for preparing a thermal barrier coating, wherein the composite powder for thermal barrier coating described in the first aspect and / or the composite powder for thermal barrier coating prepared by the preparation method described in the second aspect is subjected to atmospheric plasma spraying to obtain a thermal barrier coating.

[0039] The present invention adopts a method comprising a chemical formula of (Hf x ,Zr 1-x )6Ta2O 17The composite tantalate, x is 0.2~0.8, and the spherical powder with a hollow structure is subjected to atmospheric plasma spraying. The obtained thermal barrier coating has significantly reduced thermal conductivity, significantly improved high-temperature phase structure stability and bonding strength, and the coating is not easy to fail. The thermal conductivity of the thermal barrier coating of the present invention is significantly reduced to 0.8~0.9W / (m·K), and the bonding strength of the coating is significantly improved to 25MPa-35MPa. Compared with conventional thermal barrier coatings, the thermal barrier coating has a long service life and can withstand high temperature and harsh service environments. Under the 1400℃ thermal shock test, the service life reaches more than 2000 times.

[0040] In some preferred embodiments, the conditions of the atmospheric plasma spraying include: a spraying distance of 90 mm to 120 mm, a spraying power of 43 kW to 47 kW, a carrier gas flow rate of 2 slpm to 5 slpm, and a powder feeding rate of 10 g / min to 20 g / min; and / or, Before atmospheric plasma spraying using the composite powder for thermal barrier coating described in the first aspect and / or the composite powder for thermal barrier coating prepared by the preparation method described in the second aspect, an MCrAlY coating and a YSZ coating are sprayed in sequence.

[0041] In this preferred embodiment, the composite powder includes a chemical formula of (Hf x ,Zr 1-x )6Ta2O 17 The composite tantalate, x is 0.2~0.8, the spherical powder with hollow structure, the spraying distance is 90mm~120mm, the spraying power is 43kw~47kw, the carrier gas flow rate is 2slpm~5slpm, and the powder feeding rate is 10g / min~20g / min. The spraying process is more conducive to improving the bonding strength of the coating, while making the internal organization of the coating form a dispersed pore structure, reducing the thermal conductivity of the coating, thereby enhancing the thermal insulation performance of the coating. The MCrAlY coating is used as the bottom layer and the YSZ coating is used as the middle layer. The chemical formula is (Hf x ,Zr 1-x )6Ta2O 17 The composite tantalate coating formed by spraying the spherical powder with hollow structure is used as the surface layer, which is more conducive to reducing the brittleness of the thermal barrier coating and improving the service life of the coating. YSZ coating refers to yttria partially stabilized zirconia coating, and M in MCrAlY coating refers to Ni and / or Co.

[0042] Before preparing the thermal barrier coating of the present invention, the substrate is preferably subjected to a roughening treatment so that the surface roughness of the substrate is Ra8-12 μm. The thickness of the MCrAlY bottom layer of the present invention is preferably 50 μm-150 μm, the thickness of the intermediate layer YSZ coating is preferably 100 μm-200 μm, and the thickness of the hafnium zirconium tantalate surface layer is preferably 100 μm-200 μm.

[0043] In a fourth aspect, the present invention provides a thermal barrier coating, which is prepared by the preparation method described in the third aspect. The thermal barrier coating of the present invention has significantly reduced thermal conductivity, significantly improved high temperature phase structure stability and bonding strength, and the coating is not prone to failure.

[0044] The present invention is further described in detail below with reference to specific embodiments.

[0045] Example 1 A method for preparing a composite powder for a thermal barrier coating, comprising the following steps: Step 1: Dissolve ZrOCl2·8H2O, HfOCl2·8H2O and TaO(NO3)3 in water to prepare a composite salt solution. The molar ratio of ZrOCl2·8H2O, HfOCl2·8H2O and TaO(NO3)3 is 30:30:20. The composite salt solution contains Zr 4+ , Hf 4 + 、 5+ , Zr in composite salt solution 4+ , Hf 4+ and Ta 5+ The molar ratio of is 30:30:20, and an ammonia precipitant is added to the composite salt solution to form a suspension. The solid dispersed phase in the suspension includes a chemical formula of (Hf 1 / 2 ,Zr 1 / 2 )6Ta2O 17 of complex tantalates; Step 2: Plasma spheroidize the suspension in step 1 to obtain composite powder for thermal barrier coating. The flame power of plasma spheroidization is 45 kW, the liquid inlet rate is 8 mL / min, the gas temperature of the quenching gas is -10°C, and the gas flow rate is 25 slpm.

[0046] A composite powder for thermal barrier coating, the composite powder is a spherical powder with a hollow structure, and the composite powder includes a chemical formula of (Hf 1 / 2 ,Zr 1 / 2 )6Ta2O 17 The ratio of the inner diameter to the outer diameter of the composite powder is 0.5 on average. The inner diameter and the outer diameter of the composite powder are measured to obtain the ratio of the inner diameter to the outer diameter of the composite powder. The scanning electron microscope photo of the composite powder can be found in Figure 1 and Figure 2The composite powder is a spherical powder with a hollow structure.

[0047] A method for preparing a thermal barrier coating, using the composite powder for the thermal barrier coating to perform atmospheric plasma spraying to obtain the thermal barrier coating, wherein the spraying distance of the atmospheric plasma spraying is 110 mm, the spraying power is 45 kW, the carrier gas flow rate is 3 slpm, and the powder feeding rate is 15 g / min. The scanning electron microscope photo of the thermal barrier coating can be found at Figure 3 The thermal barrier coating has dispersed pores. The fracture toughness of the thermal barrier coating is 4.3 MPa·m 1 / 2 The test method is "ASTM E1820-23b Standard Test Method for Fracture Toughness Measurement".

[0048] Example 2 The preparation method of the composite powder is carried out in accordance with Example 1, except that in step 2, the gas temperature of the plasma spheroidization quenching gas is -40°C and the gas flow rate is 40 slpm. The composite powder is prepared in accordance with Example 1, except that the ratio of the inner diameter to the outer diameter of the composite powder is 0.25.

[0049] Example 3 The preparation method of the composite powder is carried out in accordance with Example 1, except that in step 2, the flame power of the plasma spheroidization is 40 kW and the liquid feeding rate is 12 mL / min. The composite powder is prepared in accordance with Example 1, except that the ratio of the inner diameter to the outer diameter of the composite powder is 0.21.

[0050] Example 4 The preparation method of the thermal barrier coating is referred to as in Example 1, except that the power of the atmospheric plasma spraying is 40 kW.

[0051] Comparative Example 1 Referring to the preparation method of the composite powder for thermal barrier coating in Example 1, the difference is that in step 1, the molar ratio of ZrOCl2·8H2O, HfOCl2·8H2O and TaO(NO3)3 is 50:10:20, and the ZrOCl2·8H2O in the composite salt solution is 1:10:20. 4+ , Hf 4+ and Ta 5+ The molar ratio is 50:10:20, and the solid dispersed phase in the suspension includes a chemical formula of (Hf 1 / 6 ,Zr 5 / 6 )6Ta2O 17 The composite tantalate is referred to the composite powder of Example 1, except that the composite powder includes a chemical formula of (Hf 1 / 6 ,Zr 5 / 6 )6Ta2O 17 The fracture toughness of the thermal barrier coating is 3.1 MPa·m 1 / 2 .

[0052] Comparative Example 2 Referring to the preparation method of the composite powder for thermal barrier coating in Example 1, the difference is that in step 1, the molar ratio of ZrOCl2·8H2O, HfOCl2·8H2O and TaO(NO3)3 is 10:50:20, and the ZrOCl2·8H2O in the composite salt solution is 1:10:10. 4+ , Hf 4+ and Ta 5+ The molar ratio is 10:50:20, and the solid dispersed phase in the suspension includes a chemical formula of (Hf 5 / 6 ,Zr 1 / 6 )6Ta2O 17 The composite tantalate is referred to the composite powder of Example 1, except that the composite powder includes a chemical formula of (Hf 5 / 6 ,Zr 1 / 6 )6Ta2O 17 of composite tantalates.

[0053] Comparative Example 3 Referring to the preparation method of the composite powder for thermal barrier coating of Example 1, the difference is that in step 1, ZrOCl2·8H2O is not added, the molar ratio of HfOCl2·8H2O and TaO(NO3)3 is 80:25, and the composite salt solution contains Hf 4+ 、 5+ , Hf in composite salt solution 4+ and Ta 5+ The molar ratio is 80:25, and the solid dispersed phase in the suspension includes Hf6Ta2O 17 Tantalate, referring to the composite powder of Example 1, except that the composite powder includes a chemical formula of Hf6Ta2O 17 of tantalate.

[0054] Comparative Example 4 Referring to the preparation method of the composite powder for thermal barrier coating of Example 1, the difference is that in step 1, HfOCl2·8H2O is not added, the molar ratio of ZrOCl2·8H2O and TaO(NO3)3 is 80:25, and the composite salt solution contains Zr 4+ 、 5+ , Zr in composite salt solution 4+ and Ta 5+ The molar ratio is 80:25, and the solid dispersed phase in the suspension includes Zr6Ta2O 17 Tantalate, referring to the composite powder of Example 1, except that the composite powder includes a chemical formula of Zr6Ta2O 17 Tantalate. The fracture toughness of the thermal barrier coating is 2.5 MPa·m 1 / 2 .

[0055] Comparative Example 5 The preparation method of the composite powder for thermal barrier coating is referred to in Example 1, except that in step 2, the flame power is 28 kW and the liquid feeding rate is 40 mL / min. The composite powder does not have a hollow structure.

[0056] Test Case The thermal barrier coatings obtained in the above examples and comparative examples were subjected to various performance tests shown in Table 1, and the results are shown in Table 1. The thermal conductivity test method is referred to GB / T 22588, the high temperature phase structure stability test method is referred to JY / T 5320-2006, the test temperature range is 25°C to 1400°C, and the bonding strength test method is referred to ISO 1491. The phase structure of the coating completed by atmospheric plasma spraying in Example 1 is referred to Figure 4 , 25℃~1400℃ high temperature phase structure stability test completed phase structure see Figure 5 , the phase structure is stable and there is no phase change.

[0057] Table 1

[0058] Comparing Comparative Example 1 and Example, the composite tantalate (Hf x ,Zr 1-x )6Ta2O 17 Where x is not less than 0.2, the fracture toughness and high temperature phase structure stability of the coating can be improved and the thermal conductivity of the coating can be reduced. Compared with Comparative Example 2 and the embodiment, the composite tantalate (Hf x ,Zr 1-x )6Ta2O 17 Wherein x is not greater than 0.8, the high-temperature phase structure stability of the coating can be improved and the thermal conductivity of the coating can be reduced. Comparing Example 3 with the embodiment, compared with only doping with Hf, Hf and Zr are doped at the same time to form a composite tantalate, which can improve the high-temperature phase structure stability of the coating and reduce the thermal conductivity of the coating. Comparing Example 4 with the embodiment, compared with only doping with Zr, Hf and Zr are doped at the same time to form a composite tantalate, which can improve the fracture toughness and high-temperature phase structure stability of the coating and reduce the thermal conductivity of the coating. Comparing Example 5 with the embodiment, the composite powder with a hollow structure can improve the bonding strength of the coating and reduce the thermal conductivity of the coating.

[0059] Compared with Examples 1 to 3, the ratio of the inner diameter to the outer diameter of the composite powder is not less than 0.25, which is more conducive to improving the bonding strength of the coating and reducing the thermal conductivity of the coating. The ratio of the inner diameter to the outer diameter of the composite powder is not less than 0.4, which is further more conducive to improving the bonding strength of the coating and reducing the thermal conductivity of the coating. Compared with Example 1 and Example 4, the spraying power of the atmospheric plasma spraying is not less than 43kw, which is more conducive to improving the bonding strength of the coating.

[0060] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite powder for thermal barrier coating, characterized in that: The composite powder is a spherical powder with a hollow structure. The composite powder includes a chemical formula of (Hf x ,Zr 1-x )6Ta2O 17 A composite tantalate, wherein x is 0.2~0.

8.

2. The composite powder according to claim 1, characterized in that: The ratio of the inner diameter to the outer diameter of the composite powder is 0.25-0.

7.

3. The composite powder according to claim 2, characterized in that: The ratio of the inner diameter to the outer diameter of the composite powder is 0.4-0.

6.

4. A method for preparing a composite powder for a thermal barrier coating according to any one of claims 1 to 3, characterized in that: include: Preparation of Zr 4+ , Hf 4+ 、 5+ A composite salt solution, adding a precipitant to the composite salt solution to obtain a suspension, and plasma spheroidizing the suspension to obtain the composite powder for the thermal barrier coating; The composite salt solution contains Zr 4+ , Hf 4+ and Ta 5+ The molar ratio of is 20-40:20-75:15-40, and the solid dispersed phase in the suspension includes a chemical formula of (Hf x ,Zr 1-x )6Ta2O 17 The composite tantalate, x is 0.2-0.8, and the conditions of the plasma spheroidization include: the flame power is 40kW-50kW, and the liquid feeding rate is 5mL / min-15mL / min.

5. The preparation method according to claim 4, characterized in that: The flame power is 42 kW to 48 kW, and the liquid inlet rate is 5 mL / min to 10 mL / min.

6. The preparation method according to claim 5, characterized in that: The conditions for plasma spheroidization also include: the gas temperature of the quenching gas rapidly cooled is -15°C to 0°C, and the gas flow rate is 20slpm to 30slpm.

7. The preparation method according to claim 4, characterized in that: The composite salt solution is prepared by dissolving a mixture of ZrOCl2·8H2O, HfOCl2·8H2O and TaO(NO3)3 in water; and the precipitant is ammonia water.

8. A method for preparing a thermal barrier coating, characterized in that: A thermal barrier coating is obtained by atmospheric plasma spraying using the composite powder for thermal barrier coating according to any one of claims 1 to 3 and / or the composite powder for thermal barrier coating prepared by the preparation method according to any one of claims 4 to 7.

9. The preparation method according to claim 8, characterized in that: The conditions of the atmospheric plasma spraying include: a spraying distance of 90 mm to 120 mm, a spraying power of 43 kW to 47 kW, a carrier gas flow rate of 2 slpm to 5 slpm, and a powder feeding rate of 10 g / min to 20 g / min; and / or, Before atmospheric plasma spraying of the composite powder for thermal barrier coating according to any one of claims 1 to 3 and / or the composite powder for thermal barrier coating prepared by the preparation method according to any one of claims 4 to 7, an MCrAlY coating and a YSZ coating are sprayed in sequence.

10. A thermal barrier coating, characterized in that: It is prepared by the preparation method described in claim 8 or 9.

Citation Information

Patent Citations

  • Preparation method of hollow spherical YSZ powder for plasma spraying

    CN104129990A

  • Method for preparing hollow spherical BSAS powder for environmental barrier coating

    CN109485387A

  • Preparation method of ceramic material and preparation method of thermal barrier coating

    CN110304919A

  • Preparation methods of suspension and coating and thermal barrier coating

    CN112695266A

  • Hollow yttrium oxide partially-stabilized zirconium oxide powder as well as preparation method and application thereof

    CN114075086A